Ã¢â¬ËBahasa RupaÃ¢â¬â¢ dalam Komik Perempuan Indonesia Tahun 2000 Ã¢â¬â 2010 - Zpalanzani, Alvanov - (PANGGUNG, 2012)
ABSTRACTÃÂ IndonesiaÃ¢â¬â¢s girlsÃ¢â¬â¢ comics introduced in early 2000, mainly developed by girl comic artists, in- tended for girls readers and heavily emphasized girlsÃ¢â¬â¢ romance as story theme. GirlsÃ¢â¬â¢ comic is one of pop culture media that creates a unique visual language system through construction of its visual storytelling structure. This is an explanatory research that applies visual storytelling structure anal- ysis in order to depict its visual narrative elements and structure in girlsÃ¢â¬â¢ comics. This research will extract the uniqueness of girlsÃ¢â¬â¢ comicsÃ¢â¬â¢ visual storytelling structure and visual language system. As the result, girlsÃ¢â¬â¢ comics are amplification of characters, emotional visual backgrounds, and emotional transition which marked by establishing shots as sequence margin in its visual storytelling structure and visual language system.ÃÂ Keywords: girlsÃ¢â¬â¢ comics, structure analysis, visual storytelling, visual language.